Bioluminescence imaging of stroke-induced endogenous neural stem cell response - Vandeputte, Caroline; Reumers, Veerle; Aelvoet, Sarah-Ann; Thiry, Irina; De Swaef, Sylvie; Van den Haute, Chris; Pascual-Brazo, Jesus; Farr, Tracy D.; Vande Velde, Greetje; Hoehn, Mathias; Himmelreich, Uwe; Van Laere, Koen; et al. (Elsevier, 2014)
Brain injury following stroke affects neurogenesis in the adult mammalian brain. However, a complete under¬standing of the origin and fate of the endogenous neural stem cells (eNSCs) in vivo is missing. Tools and technol¬ogy that allow non-invasive imaging and tracking of eNSCs in living animals will help to overcome this hurdle. In this study, we aimed to monitor eNSCs in a photothrombotic (PT) stroke model using in vivo bioluminescence imaging (BLI). In a first strategy, inducible transgenic mice expressing firefly luciferase (Fluc) in the eNSCs were generated. In animals that received stroke, an increased BLI signal originating from the infarct region was ob¬served. However, due to histological limitations, the identity and exact origin of cells contributing to the in¬creased BLI signal could not be revealed. To overcome this limitation, we developed an alternative strategy employing stereotactic injection of conditional lentiviral vectors (Cre-Flex LVs) encoding Fluc and eGFP in the subventricular zone (SVZ) of Nestin-Cre transgenic mice, thereby specifically labeling the eNSCs. Upon induction of stroke, increased eNSC proliferation resulted in a significant increase in BLI signal between 2 days and 2 weeks after stroke, decreasing after 3 months. Additionally, the BLI signal relocalized from the SVZ towards the infarct region during the 2 weeks following stroke. Histological analysis at 90 days post stroke showed that in the peri-infarct area, 36% of labeled eNSC progeny differentiated into astrocytes, while 21% differentiated into mature neu¬rons. In conclusion, we developed and validated a novel imaging technique that unequivocally demonstrates that nestin+ eNSCs originating from the SVZ respond to stroke injury by increased proliferation, migration towards the infarct region and differentiation into both astrocytes and neurons. In addition, this new approach allows non-invasive and specific monitoring of eNSCs overtime, opening perspectives for preclinical evaluation of can¬didate stroke therapeutics.